Antidiabetic properties and mechanism of action of Gynura procumbens water extract in streptozotocin-induced diabetic rats - Hassan, Zurina (MDPI, 2010)
Gynura procumbens (Lour.) Merr (family Compositae) is cultivated in Southeast Asia, especially Indonesia, Malaysia and Thailand, for medicinal purposes. This study evaluated the in vivo hypoglycemic properties of the water extract of G. procumbens following 14 days of treatment and in vitro in RIN-5F cells. Glucose absorption from the intestines and its glucose uptake in abdominal skeletal muscle were assessed. The antidiabetic effect of water extract of G. procumbens leaves was investigated in streptozotocin-induced diabetic rats. The intraperitoneal glucose tolerance test (IPGTT) was performed in diabetic rats treated with G. procumbens water extract for 14 days. In the IPGTT, blood was collected for insulin and blood glucose measurement. After the IPGTT, the pancreases were collected for immunohistochemical study of β-cells of the islets of Langerhans. The possible antidiabetic mechanisms of G. procumbens were assessed through in vitro RIN-5F cell study, intestinal glucose absorption and glucose uptake by muscle. The results showed that G. procumbens significantly decreased blood glucose levels after 14 days of treatment and improved outcome of the IPGTT. However, G. procumbens did not show a significant effect on insulin level either in the in vivo test or the in vitro RIN-5F cell culture study. G. procumbens also showed minimal effects on β-cells of the islets of Langerhans in the pancreas. However, G. procumbens only significantly increased glucose uptake by muscle tissues. From the findings we can conclude that G. procumbens water extract exerted its hypoglycemic effect by promoting glucose uptake by muscles.